2012
DOI: 10.1159/000346138
|View full text |Cite
|
Sign up to set email alerts
|

The Hyperactivity/Inattention Subscale of the Strengths and Difficulties Questionnaire Predicts Short- and Long-Term Weight Loss in Overweight Children and Adolescents Treated as Outpatients

Abstract: Objective: The success of treatment for pediatric obesity is variable and often unsatisfactory. This study elucidates the influence of inattention and hyperactivity/impulsivity on short- and long-term weight loss and maintenance after outpatient treatment. Methods: We included 8- to 16-year-old overweight and obese participants treated in 17 multidisciplinary outpatient treatment centers in a nationwide observational study. All treatment centers that reported long-term (1-year) follow-up weight data of at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…18 Greater inattention predicted less short- and long-term weight loss for children and adolescents in weight-loss treatment. 49,50 On the contrary, Gunstad et al 21 found no relationship between BMI and digit span backward performance in children and adolescents, whereas Krombholz 22 also found no relationship among weight and concentration ability in a sample of kindergarteners.…”
Section: Resultsmentioning
confidence: 97%
“…18 Greater inattention predicted less short- and long-term weight loss for children and adolescents in weight-loss treatment. 49,50 On the contrary, Gunstad et al 21 found no relationship between BMI and digit span backward performance in children and adolescents, whereas Krombholz 22 also found no relationship among weight and concentration ability in a sample of kindergarteners.…”
Section: Resultsmentioning
confidence: 97%
“…While it is unclear whether BMI, independent of other risk factors, is associated with suicidal ideation, both actual and perceived adolescent overweight and obesity are associated with suicidal ideation. 30 Furthermore, weight-based teasing, which is associated with lower self-esteem, lower body image, and higher depressive symptoms, may be a causative factor. 3 We also identified 12 patients with homicidal ideation, but none expressed imminent threat of harm, and therefore did not require crisis intervention.…”
Section: Discussionmentioning
confidence: 99%
“…29 Accordingly, in our study, we found that patients aged 8 to 10 and 11 to 14 years had a greater proportion of borderline/abnormal hyperactivity-inattention symptoms scores compared with US norms. These symptoms have treatment implications as a recent study showed that weight loss success was negatively predicted by inattention and hyperactivity/impulsivity as measured using the SDQ-P. 30 Given the known associations between school difficulties, 2 weight-based teasing, 3 and bullying, 4 it was not surprising that nearly one-quarter (21.9%) of patients in our sample endorsed difficulties at school and 6% felt unsafe due to emotional, verbal, or physical threats and/or assaults. Similarly, patients in our sample had a greater proportion of borderline/abnormal SDQ-P peer problems scores, which includes specific questions about bullying and social isolation, compared with the normative US data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inattentiveness has also been uniquely linked to children with obesity with suggested negative influence on attentiveness to hunger and satiety cues (Agranat-Meged et al, 2005; Davis, Levitan, Smith, Tweed, & Curtis, 2006). Furthermore, greater inattention, hyperactivity, and/or impulsivity in youth with obesity predicts poorer short- and long-term weight-related treatment outcomes (Nederkoorn, Braet, Van Eijs, Tanghe, & Jansen, 2006; van Egmond-Froehlich et al, 2012). Although the literature linking pediatric OV/OB and ADHD has grown, further investigation into the exact nature of the association and identification of contributing factors are still needed.…”
mentioning
confidence: 99%